2018
DOI: 10.1101/286039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RaftProt V2: understanding membrane microdomain function through lipid raft proteomes

Abstract: Cellular membranes feature dynamic submicrometer-scale lateral membrane domainsvariously referred to as lipid rafts, membrane rafts or glycosphingolipid-enriched microdomains (GEM). In order to understand the molecular functions of lipid rafts, numerous studies have utilized various biochemical methods to isolate and examine the protein composition of membrane rafts. However, interpretation of individual raft proteomics studies are confounded by the limitations of isolation methods and the dynamic nature of ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…S1A, B). Although a fraction of the probe might remain also in the non-raft regions, strong preference to lipid rafts was clear and also supported by our shortlisting of the most efficiently and constitutively biotinylated proteins, out of which 90% were found in the RaftProt database (Mohamed et al, 2019) (Suppl. File 2).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…S1A, B). Although a fraction of the probe might remain also in the non-raft regions, strong preference to lipid rafts was clear and also supported by our shortlisting of the most efficiently and constitutively biotinylated proteins, out of which 90% were found in the RaftProt database (Mohamed et al, 2019) (Suppl. File 2).…”
Section: Discussionsupporting
confidence: 67%
“…File 2). Almost 90% of the proteins were also found in the available RaftProt databases (Mohamed et al, 2019) (Fig. 3A, Suppl.…”
Section: Lipid Raft-resident Proteins In B Cellsmentioning
confidence: 97%
“…As ORP2 is suggested to transport cholesterol toward the PM, we wondered whether the expression of genes regulating PM cholesterol‐rich raft domains was altered in ORP2 KD HUVECs. Since lipid raft‐associated proteins as a category are not included in the pathway databases used (Wikipathway, KEGG, Reactome, and PID), we ran a separate comparison of the ORP2 KD RNAseq data against the RaftProt database, 31 available at http://raftprot.org. The analysis revealed that 69.4% of the gene IDs found in the RaftProt database were significantly affected in ORP2 KD HUVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, depletion of VE‐cadherin increases angiogenic sprouting, 63,67 in agreement with our data showing an increase of tip cells and perpendicular sprouts in ORP2 −/− retina. Puzzlingly, the retinal phenotype of the ORP2 −/− animals is very subtle, although the PM cholesterol organization is reported to have major effects on VEGF signaling and angiogenesis 3,5,6,8,31,32 . A plausible explanation is the existence of several overlapping cholesterol trafficking routes from endosomes to the PM, such as a Rab8‐myosin V‐mediated vesicular pathway 68 and a recently described ORP1S‐mediated pathway 69 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation